Role of transrectal sectional sonography (TRSS) in management of prostatic abscesses - Salah Elwagdy; Mohamed Abdelkhalek; Abdalla El-Kheshen; Abdel Aziz Aun; Amr Mostafa (Urology Annals, 2015)
Aim: The aim of this study was to assess the effectiveness of transrectal sectional sonography (TRSS) in the diagnosis and treatment of prostatic abscess. Materials and Methods: Eighteen patients with prostatic abscesEs were the material of the present study. The criteria of abscess collection within the prostate gland and the periprostatic tissues were confirmed by TRSS, which guided the aspiration in all patients. Results: Diagnosis and transperineal needle aspiration of prostatic abscesses were successful in all cases. After the second puncture procedure, recurrence noted in 2 (11.1%) out of 18 patients, who were further subjected to transurethral deroofing under TRSS vision. The amount of pus drained ranged between 3.6 and 29.3 mL (mean: 15.1 mLSD ± 1.5), compatible with the estimated volume by virtual organ computer-aided analysis three-dimensional measurements. The most frequently involved organism was Escherichia coli. All patients received intravenous antibiotics (third generation cephalosporin) after the midstream urine analysis and further proper antibiotics, according to the aspirated pus culture and sensitivity. Conclusions: Transrectal sectional sonography could be a more reliable method in the diagnosis of prostatic abscesses. It can provide precise needle-guides into the best drainage location of the abscess cavity and justify transurethral unroofing if persistent recurrence is there.